(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The integration of information technology with other subjects can be determined by analyzing the content of the subject, forms, methods and teaching aids recommended by designers when implementing integration. If we name the listed external dependencies, then there is also an internal dependency between the chapters and sections of the discipline. We will consider the features of this connection and its significance when studying a certain subject using the example of the “Information Technologies” course.